Early childhood teachers' feedback in natural mathematical learning situations: Development and validation of a detailed category system - Lena Aumann; Hedwig Gasteiger; Rosa M. Puca (Acta Psychologica, 2024)
In many countries, early mathematical learning takes place in informal and play-based situations. To support children's mathematical learning, the interactions that occur in the daily contact between the early childhood (EC) teacher and the child in kindergarten play an important role. In these interactions, the feedback provided by the EC teacher is considered to have effects on learning. However, how EC teachers actually give specific or non-specific feedback in everyday activities and play situations with a potential for mathematical learning (natural mathematical learning situations) has been little studied so far. To comprehensively characterize the EC teacher's feedback in natural mathematical learning situations, the current study developed a detailed category system based on categories from previous feedback studies, conducted under various conditions and with different objectives. To verify our category system, we coded mathematical teacher-child interactions (N = 162). The coding provided us with evidence that the category system allows to capture the given feedback in natural mathematical learning situations reliably and in detail. The category system can be useful for further research examining the effects of naturally given feedback on children's mathematical learning and, in the long run, for training teachers in the use of potentially supportive feedback in natural learning situations.